‘Climate Change, Major Groups and the Importance of a Seat at the Table: Women and the UNFCC Negotiations’ - Karen Morrow (Gender and the Environment, 2015)
This publication reprints an electronic publication from Jereja Penca and Correa de Andrade (eds.), The Dominance of Climate Change in Environmental Law: Taking Stock for Rio +20 (European University Institute, 2012) which considers the approaches adopted to developing international environmental law rooted in the 1992 UNCED 1992, comparing the typical ‘top-down’ approach to international environment law exhibited in the UNFCCC with the ‘bottom-up’ approach espoused by Agenda 21. It will be argued that, while adopting such widely differing approaches was explicable at the time, the failure to characterise the climate change regime more coherently within the sustainability context has had important ramifications in its development. Not least, the initial narrow state-centric and technocractic approach taken to climate change excluded the voices of important stakeholders from the debate shaping the international law regime, an issue that has been one of the lesser discussed factors that has impeded legal progress in this area.